THE USE OF MODERN AUTOMATED INFORMATION SYSTEMS AS THE MOST IMPORTANT MECHANISM FOR THE USE OF WATER RESOURCES IN THE REGION - Obidovich, Sultonov Akmal (International Journal of Psychosocial Rehabilitation, 2020)
This article considers the analysis of agroclusters and the application of modern automated water use systems in the agricultural sector in Uzbekistan using the example of the Jizzakh region to introduce water-saving technologies in the form of agroclusters to save water resources in the region, as well as an insufficient level of education to meet the growing demand for qualified personnel in a modern, technologically rapidly changing world. The issues of effective training that require highly integrated practice-oriented methods for solving water use problems, including water supply and sanitation systems, as well as the use of outdated water use technologies are considered.